Clinical Features and Correlates of Outcomes for High-Risk, Marginalized Mothers and Newborn Infants Engaged with a Specialist Perinatal and Family Drug Health Service - Lee Taylor; Delyse Hutchinson; Ron Rapee; Lucy Burns; Christine Stephens; Paul S. Haber (Obstetrics and Gynecology International)
Background. There is a paucity of research in Australia on the characteristics of women in treatment for illicit substance use in pregnancy and the health outcomes of their neonates. Aims. To determine the clinical features and outcomes of high-risk, marginalized women seeking treatment for illicit substance use in pregnancy and their neonates. Methods. 139 women with a history of substance abuse/dependence engaged with a perinatal drug health service in Sydney, Australia. Maternal (demographic, drug use, psychological, physical, obstetric, and antenatal care) and neonatal characteristics (delivery, early health outcomes) were examined. Results. Compared to national figures, pregnant women attending a specialist perinatal and family drug health service were more likely to report being Australian born, Aboriginal or Torres Strait Islander, younger, unemployed, and multiparous. Opiates were the primary drug of concern (81.3%). Pregnancy complications were common (61.9%). Neonates were more likely to be preterm, have low birth weight, and be admitted to special care nursery. NAS was the most prevalent birth complication (69.8%) and almost half required pharmacotherapy. Conclusion. Mother-infant dyads affected by substance use in pregnancy are at significant risk. There is a need to review clinical models of care and examine the longer-term impacts on infant development.